SISTEMA PRISIONAL BRASILEIRO - Gomes, Adriana Leite; Gomes, Juliana Dias; Ramos, Robson; Santos, Rosangela Bitencourt dos; Francisco, Tatiane Reis; Espírito Santo, João Aparecido do; Pinna, Regina Maria (Revista Ciências Jurídicas e Sociais - UNG-Ser, 2014)
...ver texto na íntegra.